(untitled) (Physical Culture and Sport: Scientific Perspective, 2024)
In children’s and youth sports, the relationship between the coach, the athlete and the parents is of great importance, because success in competition and in achieving sports results primarily depends on the coordinated interaction between all participants. That is why our scientific search is devoted to the study of this problem. First of all, we examined the interpretation of the definition of ‘family’, characterised family relationships and the impact of external and internal factors on them. We also analysed the psychological and physiological characteristics of adolescence of girls and boys to better understand how to build interaction with adolescents. We identified a number of contradictions that are characteristic of adolescence. Attention was also paid to the socio-pedagogical characteristics of coaches, parents and athletes.